In the line of fire : trauma in the emergency services - Regehr, Cheryl; Bober, Ted. (Oxford : Oxford University Press, 2005)
Based on original work & clinical experience, this new work describes the consequences of trauma exposure on emergency responders & the personal, organisational & societal factors that can ameliorate or exacerbate traumatic response.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Emergency medical personnel -- Job stress; Fire fighters -- Job stress; Police -- Job stress; Emergency medical personnel -- Mental health; Fire fighters -- Mental health; Police -- Mental health; Psychic trauma; Post-traumatic stress disorder